IDENTIFICATION OF PARENTING STRESS LEVEL IN MANAGING SPECIAL NEEDS CHILDREN DURING PANDEMIC COVID-19: A CROSS-NATIONAL STUDY - Mira Wahyu Kusumawati; Muzaitul Akma Mustapa Kamal Basha; Haliza Hasan; Siti Hazariah Abdul Hamid; Siti Mariam Muda; Heni Dwi Windarwati; Retno Lestari; Ridhoyanti Hidayah; Evi Harwiati Ningrum; Aisyah Nur Syarifah; et al. (Journal of Islamic, Social, Economics and Development, 2024)
The COVID-19 pandemic has presented unprecedented challenges for families worldwide, particularly those with special needs children. Parents of special needs children often face unique stressors in providing care and support for their children, and the pandemic has exacerbated these challenges. This study aims to identify and compare the general health and parental stress levels experienced by parents of special needs children in Malaysia and Indonesia during the COVID-19 pandemic. The descriptive cross-sectional quantitative design was used. Data was collected from October 2022 until December 2022. A total of 231 parents with special needs children from Malaysia and Indonesia were recruited in this study. A quantitative survey using self-completion questionnaires: General health condition (GQH – 12) and parental stress (PSI – SF) were employed. Descriptive, bivariate, and multivariate analyses were used to analyse the data. The findings indicated Indonesian parents are younger than Malaysian parents (age 31-40 years vs 41- 50 years), parents' general health score and parental stress score were higher for Indonesian parents compared to Malaysian parents (29.54 ±4.90 vs. 23.69 ±4.77) and (122.55±12.48 vs. 87.64±23.46), respectively. Determinants of socio-demographics with general health conditions and parental stress between countries showed that types of disability, parental educational status and race remained significantly associated with p-0.001, p-0.049 and p-<0.001, respectively. The current study showed that educational status, types of disability and race were significantly associated with general health conditions and parental stress levels in managing special needs children during the COVID-19 pandemic.